2009
DOI: 10.1099/ijs.0.002220-0
|View full text |Cite
|
Sign up to set email alerts
|

Haliea rubra sp. nov., a member of the Gammaproteobacteria from the Mediterranean Sea

Abstract: A novel aerobic, Gram-negative bacterium, designated strain CM41_15a T , was isolated from the surface of coastal waters of the north-western Mediterranean Sea. Cells were non-motile straight rods that formed red colonies on marine agar medium. The G+C content of the genomic DNA was 65 mol %. Phylogenetic analysis of the 16S rRNA gene sequence placed the strain in the genus Haliea within the class Gammaproteobacteria. On the basis of the 16S rRNA gene sequence comparison and physiological and biochemical chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 14 publications
2
24
1
2
Order By: Relevance
“…Degradation of starch and gelatin, reduction of nitrate to nitrite and stimulation of growth by thiosulfate were negative in all strains, as well as diagnostic tests for the enzymes tryptophanase and arginine dihydrolase. Data marked with an asterisk were taken from the literature [18,31]. Published data that disagree with our results are shown in brackets.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Degradation of starch and gelatin, reduction of nitrate to nitrite and stimulation of growth by thiosulfate were negative in all strains, as well as diagnostic tests for the enzymes tryptophanase and arginine dihydrolase. Data marked with an asterisk were taken from the literature [18,31]. Published data that disagree with our results are shown in brackets.…”
Section: Resultsmentioning
confidence: 78%
“…Noteworthy, Haliea rubra ( H. rubra) , which is closely related to C. litoralis was also reported to form red-pigmented colonies on Marine Agar 2216 [18], but in the original species description the formation of photosynthetic pigments was not reported. To exclude the possibility that a phototrophic phenotype has escaped attention in described strains of the genus Haliea , type strains belonging to this genus were cultured in SYPHC medium, which allowed expression of pigments in all photoheterotrophic strains belonging to the OM60/NOR5 clade tested so far.…”
Section: Resultsmentioning
confidence: 99%
“…A BLAST search of strains ETY-M and ETY-NAG revealed similarities to the bacteria Haliea sp. MOLA 104 and Haliea rubra strain CM41_15a (43, 44), which were 97% and 96% identical, respectively. The phylogenetic tree showed that the two isolated strains were in the clade comprising Haliea spp.…”
Section: Resultsmentioning
confidence: 99%
“…Representatives of this order constituted more than 50% of the gammaproteobacterial sequences before oil contamination, but this decreased to about 15% and 5% 23 days after addition of 2% and 5% oil, respectively, and about 20% 66 days after addition of 2% oil. The genus Haliea was recently described, isolated from marine coastal area [30], as well as the other two Haliea species described until this moment were also isolated from the marine environment [31], [32].…”
Section: Resultsmentioning
confidence: 99%